Attitudinal and Socio-Demographic Effects on Willingness to Pay for Water Services and Actual Payment Behaviour - Mugabi, J.; Kayaga, S. (2012)
Improving revenue collection rates and minimising the levels of 'bad debts' is currently a top priority for managers of water utilities in low-income countries. This study used empirical data from a cross-sectional survey of 505 utility customers in eight urban centres in Uganda to show that customer attitude towards prompt payment, perceived ease or difficulty of paying on time (perceived control), as well as social pressure, strongly influence intentions to pay, which in turn directly affects actual prompt bill payment behaviour. The findings also show that gender, income, occupation of the household head and tenure status have statistically significant direct relationships with intentions, but their effects are much smaller compared to the joint influence of attitudes, perceived control and perceived social pressure. Moreover, the effects of gender and occupation are completely mediated by perceived control and social pressure respectively. These results have implications for improving revenue collection through customer-focused initiatives.